Effect of compatibiliser on the properties of polypropylene/glass fibre/nanoclay composites - Rahman, Normasmira Abd; Hassan, Aziz; Heidarian, Javad (Associacao Brasileira de Polimeros, 2018)
Glass fibre (GF), nanoclay (NC) and hybrid composites compatibilised with maleic anhydride polypropylene (MAPP) were prepared by extrusion and injection moulding. The fourier transform infra-red spectra revealed the characteristic absorption peaks of MAPP in the compatibilised GF and NC composites. A decrement in the peak intensity of X-ray diffraction patterns of NC composite was obtained as the MAPP content increased indicating a partial exfoliation of NC. The thermogravimetric analysis showed that the incorporation of MAPP into hybrid composites reduced the thermal stability of the material. The dynamic mechanical analysis showed an increase in the storage modulus in the hybrid composites with lower content of MAPP due to the enhancement in the interfacial adhesion between the GF, NC and PP matrix.